The Role of Homoeopathic Drug Industry in increasing the Market Size of Homoeopathy in India (Homoeopathy for All, 2025)
Homoeopathy has been an integral part of India's healthcare ecosystem, providing a safe, effective, and holistic approach to treatment. Over the years, the demand for homoeopathic medicines has grown steadily, reflecting a shift in consumer preference towards natural and alternative therapies, especially post-covid. However, the true potential of homoeopathy remains untapped, and expanding its market size requires a collaborative effort from multiple stakeholders.
Keywords: Homoeopathic; Drug Industry; Market Size; treatment